ANALISIS KEBUTUHAN SUMBER DAYA MANUSIA DINAS KESEHATAN KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Yusmardiansah Yusmardiansah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
The Kuantan Singingi District Health Office was legalized through Regional Regulation No. 37 of 2000. This service is one of the services formed from several existing services, as stated in the regional regulations. From the author's observation, there are many multiple positions held by one person and there are even positions that have not been filled and the qualifications of workers who are not in accordance with the required competencies. The purpose of this study was to determine the human resource needs of the Kuantan Singingi District Health Office in 2017 in quality and quantity. This research is descriptive analytic. Descriptive is describing the availability of human resources in the Kuantan Singingi Health Service, while Analytic is studying the availability of human resources and then calculating the needs so that an overview of HR needs for the future is obtained. The results of the study revealed that quantitatively, Dinas needed 24 people with details of 5 people for section heads and 19 people for staff staff qualified for Bachelor of Public Health. The author recommends that proposals be made to increase the number of employees according to their needs and provide opportunities for existing employees to continue their education to higher strata in accordance with official needs